ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SMP - Indah Juli Syaputri; Putri Yulia (Program Studi Pendidikan Matematika, 2023)
The purpose of this study was to describe the mathematical representation abilities of seventh-grade junior high school students in solving math problems on geometrical material. This research is a qualitative descriptive type of research. The subjects in this study were 18 students in class XII at SMPN.04 Sungai Full for the 2022/2023 academic year. The focus of this research is the ability of visual representation, symbolic representation, and verbal representation. The research methodology used is descriptive qualitative in which tests and documentation are the data collection techniques used. The conclusion of this study is that the ability of mathematical representation is very important for students to master in determining the right strategy to be able to solve a mathematical problem. Mathematical problems in everyday life, visual, verbal and symbolic representation abilities are used, because everyday life problems need to be represented in the form of symbols or images in order to make it easier to solve problems and face them.